PENERIMAAN DIRI DALAM PERSPEKTIF KONSELING CATUR MURTI - Azril Syamsurizal; Bakhrudin All Habsy; Denok Setiawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Self-acceptance is the ability to embrace one's humanity without blaming oneself for situations beyond one's control. It involves awareness and acknowledgment of personal characteristics, confidence that is not influenced by external factors, the ability to present one's authentic self without fear of negative judgment, and leveraging one's strengths to live life responsibly. A high level of self-acceptance does not dwell on the number of weaknesses one may have. In this context, Catur Murti counseling, which is the focus of the technique discussed to enhance self-acceptance, is necessary to explore. This study reveals that Catur Murti counseling can improve self-acceptance using a quantitative method through a literature review approach. The research results offer a new paradigm of self-acceptance based on the principles of Catur Murti counseling as : (1) Ilmu catur murti (2) Murid gurune pribadi, Guru muride pribadi (3) Ilmu kantong bolong (4) Sugih tanpo bondho, digdaya tanpa aji (5) Trimah mawi pasrah (6) Ngupasi padhang ing peteng (7) Aum santih.